Evaluation of Internal Control System Over the Inventory Cycle in a Distribution Company (Case Study at PT. XYZ) - Mubarak, Fadhel; Melati, Indah (Jurnal Locus Penelitian dan Pengabdian, 2025)
Effective inventory management is crucial in the distribution industry, as inventory levels and conditions directly affect the overall efficiency, continuity, and effectiveness of an organization's activities. This study aims to critically explore the implementation of internal control over the inventory cycle at PT. XYZ, a multinational distribution company, uses the Internal Control–Integrated Framework of the Committee of Sponsoring Organizations of the Treadway Commission (COSO). This research is motivated by the findings of an internal audit conducted in 2023, which identified several areas that need improvement, including stock shortages, management of obsolete goods, loss of inventory, and recording mismatches. Through a qualitative case study approach, this study examines the extent to which a company's internal control practices are in line with the five core components of COSO: control environment, risk assessment, control activities, information and communication, and monitoring. The results show that although internal control mechanisms have been implemented, improvements are still needed, especially in the implementation of separation of duties, automation of the inventory recording process, and strengthening the control environment through better company policies. This study provides strategic recommendations to strengthen the internal control framework at PT. XYZ as well as providing relevant insights for other entities in the distribution sector that want to optimize inventory control systems and mitigate operational risks.